STATISTICAL CONTROL ANALYSIS OF THE STUDENT’S FINAL ASSIGNMENT COMPLETION PERIOD AT THE MATHEMATICS AND NATURAL SCIENCES FACULTY - Febriani, Arika; Susanti, Dewi Sri; Hijriati, Na'imah (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2022)
The final assignment is one of the requirements to get a bachelor’s degree for college students at the Faculty of Mathematics and Natural Sciences (FMIPA) University of Lambung Mangkurat (ULM). The average period of completion of the final assignment in the year 2015 until 2019 is 8 months, while the determined specification by the guideline is 6 months. The aim of this research is to identify the quality control of the final assignment completion process and whether satisfy the determined specification using statistical quality control. The used data in this research is the student’s final assignment completion period (variable data) and the nonconforming proportion of data (attribute data). The and control charts are used for variable data and control chart for attribute data and process capability analysis. The result of variable data is that the average period of final assignment completion is statistically in control with a control limit of months. For attribute data concluded that final assignment completion is statistically in control with a big average proportion that is . For the capability analysis process by index and value sequentially is and for the DPU value is . This shows that the completion period of the student’s final assignment of FMIPA ULM is not capable to fulfill the specified standard of the period.